IMPROVING KNOWLEDGE ABOUT THE IMPORTANCE OF VULVA HYGYNE AS AN EFFORTS TO PREVENT VAGINAL DISCHARGE IN ADOLESCENT FEMALES IN KEDIRI - Sulistyowati, Agus; Listari, Risti Puji; Wijayanti, Dini Prastyo; Astuti, Rina Widi; Lestari, Sri Wiji (Community Service Journal of Indonesia, 2024)
Ringin Sari Village is a fairly advanced village, but many of its people are not yet aware of the importance of knowledge, especially parents who are not yet aware of providing knowledge about reproduction to their children, especially those who are about to face menarche, they let their children get knowledge from various sources whose truth cannot be accounted for. Teachers sometimes still consider it taboo to provide education related to reproduction to their students. This Community Service was carried out at SDN Ringin Sari Kediri, carried out during student class hours. This community service activity aims to increase awareness of early age adolescent girls regarding vulva hygiene care in preventing vaginal discharge. Community service activities are carried out through direct counseling at school using leaflet media and activities are carried out with the following stages: Pre-test activity, a test is carried out to determine the picture of adolescent girls' knowledge regarding vulva care. This activity is carried out by asking adolescent girls to fill out a questionnaire containing 10 questions related to the material to be delivered, Delivery of material about the importance of being aware of nutritional status and nutritional intake in adolescents carried out by the Head of Community Service as an educator assisted by health promotion tools in the form of leaflets containing information related to the material provided. After the material was delivered by the educator, the respondents were then given the opportunity to ask questions about the material that had been delivered (question and answer), Post-test activities, tested how much knowledge and respondents had increased regarding the material that had been delivered, Monitoring and evaluation activities were carried out after the promotional activities were carried out. The number of students who attended was 60 people consisting of classes 4,5 and 6. The expected output of the community service activities is in the form of articles published in community service journals and leaflets that will be Haki Kan.